Digital Lifestyle: A New Portrait of Post-Pandemic Society’s Behavior (Discourse Towards Society 5.0 on Bali Island) - Riza Wulandari (Jurnal Sosioteknologi, 2023)
This research departs from scientific studies on urban communities that experienced changes in behavior during the COVID-19 pandemic. The purpose of this research is to find a new portrait discourse of post-pandemic community behavior on the island of Bali. The method in this study uses a qualitative method with data collection techniques such as in-depth interviews, observation, and literature studies, which are and analyzed using an interactive analysis model. The locations chosen in this study were four cities or districts in Bali Province, namely Denpasar, Badung, Gianyar, and Tabanan. Atotal of 30 informants were selected based on gender classification and categorization of productive age who often use information technology (productive adolescents, productive adults, and productive parents). Based on field studies, the results found that there is a new lifestyle in the post-COVID-19 pandemic community. Starting with the behavioral adjustments that occurred during the pandemic, where all activities began to use technology, and finally, the behavior created from technology-use activities became a digital lifestyle portrait. In this finding, this digital lifestyle is categorized into 5 categories, including new habits to meet lifestyles in the e-commerce space, implementing a cashless society, communicating, and socializing digitally, utilizing online food delivery, and using video conferencing platforms in every activity, both in the family environment, relationships, and work. The results of this study can be a recommendation for knowledge, model, or policy for stakeholders or other related parties related to the behavior of Society 5.0 in the future.